Fear as a Political Tool: A Critical Analysis of Representative Marjorie Taylor Greene’s Fearmongering Narratives - Kwiatek, Gabriela (International Studies. Interdisciplinary Political and Cultural Journal, 2024)
This paper examines the fearmongering narratives employed by Representative Marjorie Taylor Greene from Georgia in her political strategy. By analyzing sources, such as campaign materials, legislative proposals, and press releases through a content analysis method, the paper identifies three primary fear-based narratives this politician uses: threats to the country, threats to freedom, and threats to children. Moreover, the impact of fearmongering in Rep. Greene’s electoral strategy and its success in Georgia’s 14th congressional district, known for its conservative leanings, are also explored. By understanding the effectiveness of fearmongering, this research sheds light on the dynamics of contemporary political discourse in the United States and its potential consequences.